Challenges for children and adolescents with cancer in Europe: The SIOP‐Europe agenda. Issue 9 (7th April 2014) - Vassal, Gilles; Fitzgerald, Edel; Schrappe, Martin; Arnold, Frédéric; Kowalczyk, Jerzy; Walker, David; Hjorth, Lars; Riccardi, Riccardo; Kienesberger, Anita; Jones, Kathy‐Pritchard; Valsecchi, Maria Grazia; Janic, Dragana; et al.
Abstract In Europe, 6, 000 young people die of cancer yearly, the commonest disease causing death beyond the age of 1 year. In addition, 300, 000–500, 000 European citizens are survivors of a childhood cancer and up to 30% of them have severe long‐term sequelae of their treatment. Increasing both cure and quality of cure are the two goals of the European paediatric haematology/oncology community. SIOPE coordinates and facilitates research, care and training which are implemented by the 18 European study groups and 23 national paediatric haematology/oncology societies. SIOPE is the European branch of the International Society of Paediatric Oncology and one of the six founding members of the European Cancer Organisation. SIOPE is preparing its strategic agenda to assure long‐term sustainability of clinical and translational research in paediatric malignancies over the next 15 years. SIOPE tackles the issues of equal access to standard care and research across Europe and improvement of long term follow up. SIOPE defined a comprehensive syllabus for training European specialists. A strong partnership with parent, patient and survivor organisations is being developed to successfully achieve the goals of this patient‐centred agenda. SIOPE is advocating in the field of EU policies, such as the Clinical Trials Regulation and the Paediatric Medicine Regulation, to warrant that the voice of young people is heard and their needs adequately addressed. SIOPE and the European community are entirely committed to the global agenda against childhood cancers to overcome the challenges to increasing both cure and quality of cure of young people with cancer. Pediatr Blood Cancer 2014;61:1551–1557. © 2014 Wiley‐Liss, Inc., A Wiley Company. Pediatric Blood & Cancer published by Wiley Periodicals, Inc.